Optical parameters of amorphous arsenic triselenide multilayers prepared by spin coating - M.Salman, Salah. M. (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Multilayer thin films of amorphous arsenic triselenide (As2Se3) were obtained by spin coating solution of an amine salt in amide on glass substrate. The deposited multilayers in the range of 500 to 1000 nm were optically characterized by measuring the transmission spectra at room temperature. All used samples were baked and annealed for different periods of times and temperatures. The effect of layers number, baking times and temperatures on optical parameters were investigated. The thickness of the prepared samples up to four layers was ranging between 0.1 µm to 0.2 µm.